Potency of moringa leaf and stem extract on seed germination and seedling growth of mustard (Brassica juncea) - Preethi M; Vishnupriya B; Elakkiya. V (South African Journal of Botany, 2026)

Transforming animal study toxicology reports into structured, harmonized data using large language models - Tatyana Y. Doktorova; Ilya Schneider Chernov; Alberto Formaggio; Xiaochen Zheng; Alvaro Serra; Preethi Latha Bhavani Mohan; Guillemette Duchateau-Nguyen; Dragomir Ivanov Draganov; Matt Hayes; Catrin Hasselgren; Vishal B. Siramshetty; Stefano Gaudio; et al. (Archives of Toxicology, 2026)

Climatological characteristics of ITCZ over the South Asian monsoon domain: Using multivariate probabilistic approach - Priya Kumari; B. Preethi; M. Mujumdar (Atmospheric Research, 2026)

Improved two stage triangular fuzzy STARMA model for drought forecasting in Southern Telangana - Ch. Preethi; A. Meena; Santosha Rathod; Balaji Naik B; S. Vishnu Shankar; Amit Saha; Mrinmoy Ray; Rahul Patil (Journal of Hydrology, 2026)

Health risks due to geogenic and anthropogenic influences on groundwater quality in Southern India's hard rock terrain - B. Preethi; T. Subramani; R. Saravanan; P. Gopinathan; Zaixing Huang; Brajesh Kumar (Journal of Geochemical Exploration, 2025)

The role of Tropical Easterly Jet on improving the predictability of summer rainfall variability over the Upper Blue Nile Basin in Ethiopia - Abebe Kebede; Samuel Takele Kenea; Lev D. Labzovskii; Venkatraman Prasanna; B. Preethi (Theoretical and Applied Climatology, 2025)

Organic–inorganic interplay and paleoenvironmental reconstruction of Asia's largest opencast lignite mine deposits - B. Preethi; T. Subramani; T. Nathiya; Zaixing Huang (Environmental Geochemistry and Health, 2025)

Evaluation of fluoride contamination in groundwater and its non-carcinogenic health hazards in a drought-prone river basin of South India - Meera Rajan; D. Karunanidhi; T. Subramani; B. Preethi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

A comprehensive review on human health hazards due to groundwater contamination: A global perspective - Meera Rajan; D. Karunanidhi; J. Jaya; B. Preethi; T. Subramani; P. Aravinthasamy (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

A time series transcriptome profiling of host cell responses to Newcastle disease virus infection - B. Nagaraj Nayak; Preethi Palanisamy; Sangita Venkataraman; Madhuri Subbiah (Archives of Virology, 2024)

Waves of change: Electrochemical innovations for environmental management and resource recovery from water – A review - S. Manikandan; S.R. Deena; R. Subbaiya; D.S. Vijayan; Sundaram Vickram; B. Preethi; N. Karmegam (Journal of Environmental Management, 2024)

Analysis of localized features during wet and dry rainfall episodes over southern tip of India - E. A. Resmi; B. Preethi; R. S. Ajayamohan; Pallav Ray; C. K. Unnikrishnan; S. Nita; R. K. Sumesh; J. Dharmadas (International Journal of Climatology, 2023)
The large spatial and temporal variability of wet and dry spells of the Indian Summer Monsoon (ISM) poses the great challenge in understanding and predicting monsoonal rainfall. This challenge is further exacerbated over smaller regions, such as the southern tip of India, which receives the first spell of ISM rainfall. In this study, the characteristic features and possible precursors for wet and dry spells of rainfall over the southern tip of India are investigated. We also explore the variability in monsoon low‐level jet (LLJ) in relation to wet and dry spells over a coastal station Thiruvananthapuram (8.48°N, 76.95°E) in southwest India using in situ observations and other ancillary datasets. The results show that a wet spell spanning 3–4 days contributes about 30% of seasonal rainfall. Wet spells are characterized by westerly wind anomaly in the southern tip of India and easterly wind anomaly in northern India, leading to anomalous cyclonic vorticity over the Indian subcontinent. The opposite happens during dry spells. These characteristics are prominent from 2 days prior to the initiation of the spells, suggesting they may be used as precursors for forecasting wet and dry spells over Thiruvananthapuram. Analysis of low‐ to mid‐tropospheric (2 and 4 km) humidity reveals significant moistening (drying) during wet (dry) spells. Yet, both wet and dry spells experience humid (>80%) boundary layer. The differences in mid‐level humidity and thermodynamical structures between wet and dry spells seem to contribute to distinct rainfall characteristics over the southern tip of India. These results indicate that the use of in situ observations along with large‐scale reanalysis datasets may provide valuable information on the precursors for wet and dry spells over the southern tip of India, which can help both in regional‐ and city‐level planning and management of water resources.

Assessment of Lobster Resources in Coastal Region of Gulf of Mannar, Southeast Coast of India - N. Renuga Devi; A. Ahamed Rasheeq; B. Antrose Preethi; Muthusamy Anand; C. Titus; Sankaralingam Subbiah; Kannan Rangesh; R. Dineshkumar; A. Arumugam (Thalassas: An International Journal of Marine Sciences, 2023)

Review on NAD(P)H dehydrogenase quinone 1 (NQO1) pathway - S. Preethi; K. Arthiga; Amit B. Patil; Asha Spandana; Vikas Jain (Molecular Biology Reports, 2022)

Correction to: Erratic Asian summer monsoon 2020: COVID-19 lockdown initiatives possible cause for these episodes? - Ramesh Kripalani; Kyung-Ja Ha; Chang-Hoi Ho; Jai-Ho Oh; B. Preethi; Milind Mujumdar; Amita Prabhu (Climate Dynamics, 2022)

Erratic Asian summer monsoon 2020: COVID-19 lockdown initiatives possible cause for these episodes? - Ramesh Kripalani; Kyung-Ja Ha; Chang-Hoi Ho; Jai-Ho Oh; B. Preethi; Milind Mujumdar; Amita Prabhu (Climate Dynamics, 2022)
The summer (June through September) monsoon 2020 has been very erratic with episodes of heavy and devastating rains, landslides and catastrophic winds over South Asia (India, Pakistan, Nepal, Bangladesh), East Asia (China, Korea, and Japan), and Southeast Asia (Singapore, Thailand, Vietnam, Laos, Cambodia, Philippines, Indonesia). The withdrawal of the summer monsoon over India was delayed by 2 weeks. The monsoon season over East Asia has been the longest. China recorded a Dam burst in the twentieth century. Furthermore, the Korean Peninsula has experienced back-to-back severe tropical cyclones. Could the lockdown activities initiate to control the COVID-19 spread a possible cause for these major episodes? The strict enforcement of the lockdown regulations has led to a considerable reduction of air pollutants—dust and aerosols throughout the world. A recent study based on satellites and merged products has documented a statistically significant mean reduction of about 20, 8, and 50% in nitrogen dioxide, Aerosol Optical Depth (AOD) and PM 2.5 concentrations, respectively over the megacities across the globe. Our analysis reveals a considerable reduction of about 20% in AOD over South as well as over East Asia, more-over East Asia than over South Asia. The reduced aerosols have impacted the strength of the incoming solar radiation as evidenced by enhanced warming, more-over the land than the oceans. The differential warming over the land and the ocean has resulted in the amplification of the meridional ocean-land thermal contrast and strengthening of the monsoon flow. These intense features have supported the surplus transport of moisture from the oceans towards the main lands. Some similarity between the anomalous rainfall pattern and the anomalous AOD pattern is discernable. In particular, the enhancement of rainfall, the reduction in AOD and the surface temperature warming match very well over two regions one over West-Central India and the other over the Yangzte River Valley. Results further reveal that the heavy rains over the Yangzte River Valley could be associated with the preceding reduced aerosols, while the heavy rains over West-Central India could be associated with reduced aerosols and also due to the surface temperature warming.

Protective Effects of Sauropus Androgynus Leaf Extract against Isoproterenol Induced Cardiotoxicity - Preethi S.; Hitesh Kumar; Ramesh C.; Sowmya B. A.; Niveditha K.; Ramkishan Ajmeer; Vikas Jain (Cardiovascular Toxicology, 2022)

Development of EST-SSR markers for genetic diversity analysis in coconut (Cocos nucifera L.) - P. Preethi; Shafeeq Rahman; S. Naganeeswaran; A. A. Sabana; K. P. Gangaraj; B. A. Jerard; V. Niral; M. K. Rajesh (Molecular Biology Reports, 2020)

Thermodynamics of ferredoxin binding to cyanobacterial nitrate reductase - Anurag P. Srivastava; Neelam Mishra; Ramachandra L. A. Prasad; Preethi Rajesh; David B. Knaff (Photosynthesis Research, 2020)

Variability of Indian summer monsoon droughts in CMIP5 climate models - B. Preethi; R. Ramya; S. K. Patwardhan; M. Mujumdar; R. H. Kripalani (Climate Dynamics, 2019)

The Asymmetric Influence of the South China Sea Biweekly SST on the Abnormal Indian Monsoon Rainfall of 2002 - B. H. Vaid; B. Preethi; R. H. Kripalani (Pure and Applied Geophysics, 2018)

Neurophysiological and Neuropsychological Analysis of the Cognitive Functions in Dysthyroid Female Patients - P. Mishra; B. L. Preethi; P. Kalra (Neurophysiology, 2018)

Satellite and In Situ Observations of a Phytoplankton Bloom from Coastal Bay of Bengal: Role in pCO2 Modulation - Rajdeep Roy; K. H. Rao; T. Preethi Latha; Vinay Kumar Dadhwal; V. V. S. S. Sarma; P. V. Nagamani; S. B. Choudhury; Seetharam Pondala (Journal of the Indian Society of Remote Sensing, 2017)

Anomalous convective activity over sub-tropical east Pacific during 2015 and associated boreal summer monsoon teleconnections - Milind Mujumdar; K. P. Sooraj; R. Krishnan; B. Preethi; Manish K. Joshi; Hamza Varikoden; Bhupendra B. Singh; M. Rajeevan (Climate Dynamics, 2017)

Recent trends and tele-connections among South and East Asian summer monsoons in a warming environment - B. Preethi; M. Mujumdar; R. H. Kripalani; Amita Prabhu; R. Krishnan (Climate Dynamics, 2017)

Potential role of the February–March Southern Annular Mode on the Indian summer monsoon rainfall: a new perspective - Amita Prabhu; R. H. Kripalani; B. Preethi; G. Pandithurai (Climate Dynamics, 2016)

Precipitation extremes during Indian summer monsoon: role of cyclonic disturbances - J. V. Revadekar; Hamza Varikoden; B. Preethi; M. Mujumdar (Natural Hazards, 2016)

Molecular level understanding of resistance to nalidixic acid in Salmonella enteric serovar typhimurium associates with the S83F sequence type - B. Preethi; K. Ramanathan (European Biophysics Journal, 2016)

Estimation of Air-Sea CO2 Flux in the Coastal Waters of Visakhapatnam - T. Preethi Latha; K. H. Rao; V. V. S. S. Sarma; P. Seetaram; S. B. Choudhury; P. V. Nagamani; C. B. S. Dutt; V. K. Dhadwal; Sudip Manna (Journal of the Indian Society of Remote Sensing, 2015)

Droughts of Indian summer monsoon associated with El Niño and Non‐El Niño years - H. Varikoden; J. V. Revadekar; Y. Choudhary; B. Preethi (International Journal of Climatology, 2015)
Understanding the conditions of droughts are imperative for many purposes especially in planning and agricultural fields. In this paper an attempt is made to analyse rainfall distribution during droughts associated with El Niño and non‐El Niño events using India Meteorological Department (IMD) daily rainfall data set having a spatial resolution of 0.25° latitude × 0.25° longitude grid. Patterns of rainfall during drought years which are not associated with El Niño have below normal rainfall over most places of Indian subcontinent, except peninsular India and eastern region. Most of the drought conditions of the Indian summer monsoon rainfall are associated with El Niño (13 of the 18 years) indicating that about 72% of the drought years are associated with the influence of Pacific Ocean. North India and most of the central Indian regions are under below normal rainfall especially over west coastal stations there the severity of drought is strong. The drought that are associated with El Nino are much intense in most parts of the subcontinent, it severely affected the entire west coastal belts, monsoon zone and eastern regions than the droughts associated with non‐El Nino years. The spatial patterns of rainfall during flood years associated with La Niña events and drought years associated with El Niño reveal that the spatial structure of rainfall is highly non‐linear. These results are also verified using APHRODITE rainfall data. Over central India and Western Ghats (WGs), the drought associated with El Niño gives clear indication of droughts from the early June onward, however, in the case of non‐El Niño‐related droughts, the indication of drought can be seen only after the first week of July. The study suggests that droughts associated with El Niño events bring severe drought conditions over WG region. However, over central India, there is no considerable difference in cumulative rainfall associated with the two types of droughts. The intraseasonal properties of rainfall are prominently different from non‐El Niño to El Niño droughts. During El Niño droughts, the variance of rainfall in both the central Indian and WG regions is weaker than the droughts that are not associated with El Niño.

Setting of Cloud Albedo in the Atmospheric Correction Procedure to Generate the Ocean Colour Data Products from OCM-2 - P. V. Nagamani; T. Preethi Latha; K. H. Rao; T. Suresh; S. B. Choudhury; C. B. S. Dutt; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2015)

Precipitation analysis over southwest Iran: trends and projections - Amit G. Dhorde; Mohammad Zarenistanak; R. H. Kripalani; B. Preethi (Meteorology and Atmospheric Physics, 2014)

Retrieval and Validation of Chlorophyll-a Concentrations in the Coastal Waters Off Yanam and Kakinada (Godavari) Basin Along East Coast of India - T. Preethi Latha; P. V. Nagamani; K. H. Rao; S. K. Dash; S. B. Choudhury; Aziz Rehman; V. V. S. S. Sarma; M. Naveen Babu; P. Amarendra; B. Srinivasa Rao; T. D. V. Prasad (Journal of the Indian Society of Remote Sensing, 2014)

Topographic regulation of neuronal intermediate filaments by phosphorylation, role of peptidyl-prolyl isomerase 1: significance in neurodegeneration - B. K. Binukumar; Varsha Shukla; Niranjana D. Amin; Preethi Reddy; Suzanne Skuntz; Philip Grant; Harish C. Pant (Histochemistry and Cell Biology, 2013)

Intraseasonal SST-precipitation relationship and its spatial variability over the tropical summer monsoon region - Mathew Roxy; Youichi Tanimoto; B. Preethi; Pascal Terray; R. Krishnan (Climate Dynamics, 2013)

Kharif foodgrain yield and daily summer monsoon precipitation over India - B. Preethi; J. V. Revadekar (International Journal of Climatology, 2013)
Foodgrain yield over India during k harif (summer) season is directly affected by day to day variations in summer monsoon precipitation (June through September). An increase (decrease) in foodgrain yield is generally associated with an increase (decrease) in rainfall. However, the reduction of rainfall or occurrence of heavy rainfall activity may cause adverse effect on the crop growth. This study is therefore aimed at understanding the impact of all possible values of daily precipitation from lowest to highest rainfall during summer monsoon on kharif foodgrain yield over India for the period 1966‐2003. The study also includes an impact of intense rainfall events (1 and 5 days maximum precipitation) on foodgrain yield. Analysis covers frequency of rainy days based on all fixed thresholds (1 mm and above) at the interval of 1 mm as well as percentile thresholds (1st percentile to 99th percentile) at the interval of 1 percentile. The study reveals that the kharif foodgrain yield increases with increase in all‐India summer monsoon precipitation and rainy days. Strong positive relationship (statistically significant at 1% level) is observed for lower range of threshold values from 1 to 50 mm (1st percentile to 90th percentile), and the magnitudes of correlation decreases with increase in threshold values. The negative impact of the heavy rainfall activity is more pronounced over the heavy rainfall regions of northeast India. It is found that the prolonged occurrence of intense rainfall activity increases their impact on the foodgrain yield. Normal (moderate) range of precipitation indices is seen to be associated with both positive and negative anomalies of foodgrain yield, which point towards the influence of other climatic factors in determining the better yield of kharif foodgrain. Copyright © 2012 Royal Meteorological Society

Wet and dry years of Indian summer monsoon and its relation with Indo‐Pacific sea surface temperatures - Hamza Varikoden; B. Preethi (International Journal of Climatology, 2013)
Regional characteristics of Indian Summer Monsoon Rainfall (ISMR) during dry and wet monsoon years associated with El Niño Southern Oscillation (ENSO) and non‐ENSO (normal) periods are investigated. Four cases such as wet monsoon years associated with ENSO (EW) and non‐ENSO (NW) events and dry monsoon years associated with ENSO (ED) and non‐ENSO (ND) events have been discussed. The dry and wet years associated with ENSO and non‐ENSO periods show significant differences in the spatial pattern of rainfall. During wet years (EW and NW), the rainfall is abnormally high in the west coastal stations. However, during EW years, anomalous heavy rainfall is observed in the northern part of the west coast while during the NW years, the rainfall is high in southwest coastal regions. In central India, the rainfall is abnormally high only during the wet years associated with non‐ENSO events (NW). The west coastal areas receive below normal rainfall during ED, ND years, however, the negative anomalies are large during ED years compared to ND years. The low level (1000 hPa) moisture transport is coherent with the changes in the spatial patter of ISMR. The Indo‐Pacific sea surface temperatures (SSTs), low level circulation (at 850 hPa) features and general circulation associated with the four cases of ISMR have also been studied in detail. During wet phases of ISMR, the SST over the pacific ocean is abnormally cool and that during dry phases of ISMR is abnormally warm. However, the areas of cool and warm are different during ENSO and normal years. Copyright © 2012 Royal Meteorological Society

Synthesis of antihyperglycemic, α-glucosidase inhibitory, and DPPH free radical scavenging furanochalcones - R. Ranga Rao; Ashok K. Tiwari; P. Prabhakar Reddy; K. Suresh Babu; G. Suresh; A. Zehra Ali; K. Madhusudana; Sachin B. Agawane; Preethi Badrinarayan; G. Narahari Sastry; J. Madhusudana Rao (Medicinal Chemistry Research, 2012)

Evaluation of the ENSEMBLES multi-model seasonal forecasts of Indian summer monsoon variability - M. Rajeevan; C. K. Unnikrishnan; B. Preethi (Climate Dynamics, 2012)

Statistical analysis of the relationship between summer monsoon precipitation extremes and foodgrain yield over India - J. V. Revadekar; B. Preethi (International Journal of Climatology, 2012)
The Indian economy largely depends on agriculture which is highly influenced by the spatio‐temporal variability of precipitation. Kharif and rabi are the two main crop‐growing seasons which require major proportion of rainfall. Increase in heavy precipitation events, however, can have adverse effects on the crops. This study, therefore, is mainly focused on understanding the variation of extremes in precipitation during summer monsoon season and its impact on kharif foodgrain yield over India. For this, several objectively defined indices of observed precipitation extremes, in terms of frequencies and intensities, have been computed for the period 1951–2003 using daily gridded data of 1° latitude × 1° longitude resolution. Efforts have also been made to prepare the climatology of extremes in precipitation (1961–1990) to determine their basic characteristics over the Indian region. Correlation analysis reveals that a large part of the country exhibits positive relationship between kharif foodgrain yield and the indices of extreme precipitation, significant at 5% level. Correlations with the indices of frequencies defined as seasonal count of days when rainfall exceeds 85th, 75th, and 65th percentiles (and 30, 20, and 10 mm) show that spatial extent and strength of the positive relationship decreases with increase in threshold values. This indicates that very heavy daily rainfall is less useful than the moderate daily rainfall. Strong negative relationship between the yield and indices of extreme precipitation observed over heavy precipitation areas of northeastern parts of the country indicate that very heavy daily rainfall have an adverse effect on crop. The study also points out that increase in heavy rainfall activities during July are favourable for the yield, but correlations become weak and statistically insignificant during the month of August. Individual crops show similar results as that obtained from aggregate kharif foodgrain, however, magnitude of the correlations varies from crop to crop. Copyright © 2011 Royal Meteorological Society

Anomalous behaviour of the Indian summer monsoon 2009 - B PREETHI; J V REVADEKAR; R H KRIPALANI (Journal of Earth System Science, 2011)

Seasonal behaviour of NCEP-NCAR longwave cloud radiative forcing and its relationship with all-India summer monsoon rainfall - A. A. Munot; S. D. Patil; B. Preethi; N. Singh (International Journal of Remote Sensing, 2011)

Extremes in summer monsoon precipitation over India during 2001–2009 using CPC high-resolution data - B. Preethi; J. V. Revadekar; A. A. Munot (International Journal of Remote Sensing, 2011)

Indian summer monsoon rainfall variability in global coupled ocean-atmospheric models - B. Preethi; R. H. Kripalani; K. Krishna Kumar (Climate Dynamics, 2010)

Evaluation of Flow Rate, pH, Buffering Capacity, Calcium, Total Proteins and Total Antioxidant Capacity Levels of Saliva in Caries Free and Caries Active Children: An In Vivo Study - B. P. Preethi; Dodawad Reshma; Pyati Anand (Indian Journal of Clinical Biochemistry, 2010)